LOGIKA PENEMUAN ILMIAH TEORI (POSSITIVISME LOGIS) AUGUST COMTE - Dozan, Wely; Rohimi, Rohimi (IAIN Tulungagung, 2019)
The term philosophy is often used as a tool for scientific thinking in science. The development of philosophical thought in ancient Greece had two models of rationality namely, First, concrete philosophy. Second, philosophy in the form of metaphysics. However, this thought is not in line with the thinking of modern philosophy, namely Agus Comte in his theory